DETERMINAN PENDAPATAN PERAJIN TENUN SONGKET DI KECAMATAN SIDEMEN KABUPATEN KARANGASEM - Berliana, I Dewa Ayu Tresia; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Weaving is a cultural product that presents the culture of society as its supporters. This study aims to determine the direct effect of capital, raw materials and labor on production, the direct influence of capital, raw materials, labor and production to income and analyze and explain the indirect effect of capital, raw materials and labor to income through production Weaving Songket in Sidemen Sub-district of Karangasem Regency. The data used in this study is the primary data obtained from by distributing quizers to 67 songktet songwriters in Sidemen Sub-district. Analysis technique used in this research is path analysis. Test results showed capital, raw materials and labor directly influence significantly to the production of songket weaving craftsmen in Sidemen District Karangasem regency. Capital, raw materials, labor and production have a direct effect on income. Capital, raw materials and labor have an indirect effect on income through production which is indicated by production which is an intervening variable. Referring to the results of this study, to increase revenue can be done by increasing demand rather than supply, so the demand is greater than supply.